2004
DOI: 10.1292/jvms.66.1413
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Serological Characterization of Novel Serotype G8 Bovine Group A Rotavirus Strains Isolated in Japan

Abstract: ABSTRACT. G8 bovine group A rotaviruses isolated in Japan were genetically and serologically characterized. The VP7 gene nucleotide and amino acid sequences revealed high identity with each other. All Japanese G8 strains were classified into the same lineage in the phylogenetic analysis based on VP7 gene sequences. Antisera to four Japanese G8 strains neutralized other G8 strains, but their neutralizing titers were between 8-fold lower and 2-fold higher than homologous strains. These results suggest that the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
93
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(100 citation statements)
references
References 31 publications
(37 reference statements)
7
93
0
Order By: Relevance
“…, together with a few gene reassortments, and the phylogenetic analyses confirmed that the P [14] human strains evaluated in this study were closely related to rotavirus strains isolated from sheep, cattle, goats, guanacos, and antelopes and to rabbits (albeit to a lesser extent), suggesting that one (or more) of these animal species might be the source of the human G6P [14] strains. The main feature of the genotype and phylogenetic analyses was the close overall genomic relatedness between the five human G6P [14] rotavirus strains and the ovine and antelope rotavirus strains.…”
Section: ) These Analyses Revealed An Overall Consensus Genomic supporting
confidence: 75%
See 4 more Smart Citations
“…, together with a few gene reassortments, and the phylogenetic analyses confirmed that the P [14] human strains evaluated in this study were closely related to rotavirus strains isolated from sheep, cattle, goats, guanacos, and antelopes and to rabbits (albeit to a lesser extent), suggesting that one (or more) of these animal species might be the source of the human G6P [14] strains. The main feature of the genotype and phylogenetic analyses was the close overall genomic relatedness between the five human G6P [14] rotavirus strains and the ovine and antelope rotavirus strains.…”
Section: ) These Analyses Revealed An Overall Consensus Genomic supporting
confidence: 75%
“…The main feature of the genotype and phylogenetic analyses was the close overall genomic relatedness between the five human G6P [14] rotavirus strains and the ovine and antelope rotavirus strains. Taken together, these data strongly suggest a common origin for the human P [14] strains and those of the even-toed ungulates belonging to the mammalian order Artiodactyla, with sheep probably playing a key role in the interspecies transmission responsible for the introduction of P [14] rotavirus strains into the human population.…”
Section: ) These Analyses Revealed An Overall Consensus Genomic mentioning
confidence: 99%
See 3 more Smart Citations